Investigating Volatility in Saudi Arabia Crude Oil Prices and its impact on oil Stock Market - Tong, Shu; Baslom, Mohammed Majdy M.; Alsharif, Hussain Zaid H. (International Journal of Energy Economics and Policy, 2018)
This study is the evidence of a research that was carried out to investigate the impact of oil price volatility on oil stock markets in the context of Saudi Arabia. Prior studies have measured the impact of crude oil price (COP) volatility on stock market performance but not much attention has been paid on Saudi Arabia. This study was an attempt to fill this research gap by finding any linkages between crude oil price and Saudi stock market performance. The study also aimed to identify such structural changes in the crude oil market during a given time period caused by varying factors such as old and new financial investors, emergence of new markets, socio-political events and fluctuation in demand-supply ratios causing changes in the crude oil price significantly. Often it has been observed that when new participants enter the oil market, there are structural changes in the process of crude oil price setting, much similar to the process in any kind of financial markets. The role of OPEC in setting oil prices shall also be studied during the course of this study. Prior studies have revealed that lack of OPEC spare capacity has caused serious large imbalances in the crude oil prices worldwide as OPEC historically has been a major policy maker on the supply side. In order to carry out such a study, different models/ methods can be used including Markov Regime Switch Method and GARCH and Granger Causality Method. However, the choice of model will depend on properties/ variables. Keywords: Oil Price, demand supply ratios, Volatility, Stock Market JEL Classifications: E39, J20, R53